Architecture's Evil Empire? : the Triumph and Tragedy of Global Modernism. - Glendinning, Miles (Reaktion Books, 2011)
From Chicago to Toronto to Shanghai, cities around the world have sprouted "iconic" buildings by celebrity architects like Frank Gehry and Daniel Libeskind that compete for attention both on the skyline and in the media. But in recent years, criticism of these extreme "gestural" structures, known for their often-exaggerated forms, has been growing. Miles Glendinning's impassioned polemic, Architecture's Evil Empire, looks at how today's trademark architectural individualism stretches beyond the well-known works and ultimately extends to the entire built environment. Glendinning examines how th.